Bilateral ovarian torsion with ovarian fusion in the setting of polycystic ovarian syndrome: A case report - Rachel E. Warwar; Grant E. Schmidt (Elsevier, 2019)
Background: Adnexal torsion requires a high degree of suspicion in women presenting with pelvic pain. Polycystic ovaries are an infrequent cause of ovarian torsion but should be considered in cases without adnexal masses. Case: A 25-year-old woman had a delayed diagnosis of adnexal torsion due to polycystic ovaries despite typical presentation and imaging. A unique finding was ovarian fusion; separation was required in order to resolve the torsion. Oophoropexy was performed to prevent the recurrence of torsion. Conclusion: Ovarian torsion should be suspected in the setting of abdominal pain, enlarged polycystic ovaries, and absent adnexal blood flow on ultrasound. This case demonstrates the resilience of the adnexa and the highly variable time to necrosis in the setting of torsion. Keywords: Ovarian torsion, Polycystic ovarian syndrome, Oophoropexy